ANALISIS KINERJA BANK SYARIAH - Indiyati, Dian; Paramitha, V Santi (Jurnal Ekonomi, 2010)
A bank performance measured by CAMEL method is a comprehensive indicator of the beneficial. Any parties have put an interest to the result of value in healthy level, including the management as a successful standard in their administration, Bank Indonesia as the supervision agent, and public as the customer. The study aimed to analyze performance of bank syariah with independent operational, Bank Syariah Mandiri and Bank Muamalat Indonesia, by using of 4 years-quarterly financial report. Generally, the study shows that in the research period, Bank Syariah Mandiri has got the healthy in the valuation, while Bank Muamalat Indonesia is sufficient in healthy.